“Drop” Metastases from an Operated Case of Intracranial Anaplastic Ependymoma Identified on Fluoro-2-deoxyglucose Positron Emission Tomography/Computed Tomography - Chandra, Piyush (Indian J Nucl Med, 2017)
The seeding of tumor through cerebrospinal fluid (CSF) from primary intracranial tumors is very rare, often goes undetected, and is usually identified only on autopsy. CSF cytology along with magnetic resonance imaging constitutes the standard approach of diagnosing this grave condition. Use of fluoro-2-deoxyglucose positron emission tomography/computed tomography (PET/CT) in indentifying spinal metastases from primary intracranial malignancies is very limited and has been reported in patients with metastatic glioblastoma multiforme and medulloblastomas. We present a rare case of metastatic anaplastic ependymoma to show the potentially clinically utility of PET/CT in diagnosing leptomeningeal or the so-called “drop” metastases.